Does dairy intensification threaten livelihood diversity in East Africa? - Kihoro, Esther; Vernooij, V.; Schoneveld, G.C.; Crane, Todd A.; Vellema, S. (Elsevier, 2024)
Intensifying smallholder dairy farming can reduce global greenhouse gas emissions and increase food production on existing croplands. Much public policy therefore assumes that dairy intensification reduces emissions per unit of production, while simultaneously improving both rural incomes and food security. Whether the hypothesized social co-benefits of intensification manifest in practice has not however been fully empirically validated. Because intensification is labor and capital intensive, resource diversions may occur that could make rural livelihoods more specialized. This in turn could threaten dietary diversity and smallholder resilience to shocks. In this article, we accordingly examine the relationship between dairy intensification, livelihood diversity, nutrition diversity, and wellbeing, drawing on primary research conducted in two developing countries, Kenya and Tanzania, with vibrant smallholder dairy sectors. We find that dairy intensification by and large enhances livelihood diversity, nutritional diversity, and wealth. These findings suggest that for dairy, intensification and diversification may be complementary livelihood strategies.